Heat tolerance of titanium boride and titanium nitride contacts to gallium arsenide - Venger, Ye.F.; Milenin, V.V.; Ermolovich, I.B.; Konakova, R.V.; Voitsikhovskiy, D.I.; Hotovy, I.; Ivanov, V. N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
For contacts prepared from titanium borides by and nitrides ion-plasma sputtering onto gallium arsenide both formation mechanisms and thermal stability were investigated. We used a combination of structural, secondary-emission, optical and electrophysical methods, such as electronography, X-ray diffraction, atomic force microscopy, Auger electron spectroscopy, secondary-ion mass spectrometry, taking photoluminescence spectra and I - V curves. A physical model for contact formation was proposed. According to it, BxGa₁₋xAs (GaNxAs₁₋x) solid solutions are formed at the phase interfaces when titanium borides (nitrides) are deposited. The defects are produced in the semiconductor near-surface regions during heterostructure formation and further heat treatment. The correlation between the physico-chemical interactions at contact interfaces and the contact electrophysical parameters occurs through these defects. The objects of our investigation demonstrated high thermal stability. This was due to their two-layer structure formed by components having well-pronounced antidiffusion properties. As a result, the interdiffusion processes at the phase interfaces are drastically weakened.